An Empirical Study of Reading Comprehension Levels among Elementary School Students Based on Barrett's Taxonomy Framework - Yuliawati; Dadang Sunendar; Dinn Wahyudin; I Wayan Lasmawan; Budi Febriyanto (Universitas Pendidikan Ganesha, 2026)
Fifth-grade elementary students still show suboptimal reading comprehension, particularly in understanding informative texts that are essential for academic success. This descriptive quantitative study aims to analyze the reading comprehension of 30 fifth-grade students using Barrett’s Taxonomy Framework and cluster random sampling. Data were collected using a standardized comprehension test covering all five levels of Barrett’s taxonomy; literal, reorganization, inferential, evaluative, and appreciative and analyzed descriptively using SPSS 25. Findings revealed 40% of students were “less competent.” Evaluative comprehension showed the highest proficiency (76.9%), while reorganization was weakest (66.3%). Overall, most students (63.3%) fell into low and medium categories by Azwar’s classification, indicating significant difficulties in higher-order comprehension skills like inference and information restructuring. These results align with theoretical frameworks such as Vygotsky’s Zone of Proximal Development and Bandura’s Social Cognitive Theory, underscoring the crucial role of scaffolding and self-efficacy in reading development. This study concludes that fifth-grade students’ comprehension of informative texts remains suboptimal, particularly in higher-order thinking skills. The findings imply that teachers should apply explicit comprehension instruction, guided questioning, and summarization techniques, while schools and curriculum developers should support literacy-rich environments and adaptive literacy pedagogy training. Future studies should explore causal relationships by considering psychological and instructional variables.